2013
DOI: 10.1144/qjegh2012-038
|View full text |Cite
|
Sign up to set email alerts
|

DRISTPI, a new groundwater vulnerability mapping method for use in karstic and non-karstic aquifers

Abstract: This paper proposes a new method, called DRISTPI, to evaluate the intrinsic vulnerability to contamination of different types of aquifers. Taking the DRASTIC method as a starting point, we highlight the need to define two scenarios to differentiate karst materials from the rest of the study area. The changes made in DRISTPI, with respect to DRASTIC, include the elimination of factors that are mainly related to the movement of water through the saturated zone of the aquifer (the original A and C factors) becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 32 publications
1
16
0
1
Order By: Relevance
“…The most frequently employed methods are the index-based approaches [9,10] of which DRASTIC (D: Depth to water; R: Net recharge; A: Aquifer media; S: Soil media; T: Topography; I: Impact of vadose zone; C: Hydraulic conductivity) [9] is the most common. DRASTIC has been applied to various types of aquifer, though some authors have revealed that it is not suitable for assessing vulnerability in some karstic aquifers [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequently employed methods are the index-based approaches [9,10] of which DRASTIC (D: Depth to water; R: Net recharge; A: Aquifer media; S: Soil media; T: Topography; I: Impact of vadose zone; C: Hydraulic conductivity) [9] is the most common. DRASTIC has been applied to various types of aquifer, though some authors have revealed that it is not suitable for assessing vulnerability in some karstic aquifers [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, recent research studies have attempted to adapt the DRASTIC method to karst aquifers in recent years [12,[27][28][29][30]. Some of these [12,28,29] modified DRASTIC by including and/or removing parameters to account for karst characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Methodologies like the Slovene approach take into account precipitation analyzed in terms of volume, intensity and extreme events [15]. Other methodologies like KARSTIC and DRISTPi consider recharge as a parameter derived from precipitation regimes [16,17]. Nevertheless, vulnerability assessment in tropical areas, with pronounced seasonal precipitation patterns, can be over/under estimated since precipitation ratings from the before mentioned methods are based on year averages.…”
Section: Introductionmentioning
confidence: 99%
“…DRISTPi allows the re-assignment and modification of weights. More detailed information about this method can be found in the work of Jiménez-Madrid et al[17].…”
mentioning
confidence: 99%
“…Al though the results ob tained with the in dex meth ods are qual i ta tive, they are still com monly used world wide, es pe cially via the very ef fec tive DRASTIC method (e.g., Krogulec, 2006;Ró¿kowski, 2007;Saidi et al, 2011Saidi et al, , 2017Khemiri et al, 2013;Krogulec and Trzeciak, 2016). This method has been im proved and ad justed to com plex hydrogeological con di tions (Witkowski et al, 2003;Yu et al, 2012;Jiménez-Ma drid et al, 2013;Hernández-Espriú et al, 2014;Kazakis and Voudouris, 2015;Bonfanti et al, 2016;He et al, 2018). Com bined meth ods gen er at ing a qual i ta tive result are also used (Gemitzi et al, 2006;Civita, 2010).…”
Section: Introductionmentioning
confidence: 99%